Collaborative Learning Strategy for Better Reading Comprehension in EFL University Courses - Wahyurianto, Ibnu; Sylvia, Sylvia (Journal of English for Academic and Specific Purposes (JEASP), 2024)
This study investigates the impact of collaborative learning strategy on the reading comprehension of non-English department students at the university level. An effective reading comprehension not only talk about the ability to understanding the text, but also the capacity to interpret meaning and synthesize information from different text genre. Moreover, for the non-English department students who generally have different language competence with English department students, they often encounter a difficult situation in reading activity because of their limitation in language exposure. Using a mixed-method approach, this study combines quantitative data from reading tests with qualitative insights from student interviews and classroom observations. Over one semester, students from various non-English department participated in collaborative activities, such as collaborative strategic reading and group discussions, designed to improve critical thinking and collaborative problem-solving. The quantitative results demonstrate significant improvements in reading comprehension, particularly in identifying main ideas, making inferences, and understanding vocabulary in context. Qualitative findings reveal that students found the collaborative learning environment is enjoyable and motivating, with many reporting that collaborative learning reduced their anxiety and enhanced their willingness to participate actively. This study highlights the effectiveness of collaborative learning strategy in improving reading comprehension among non-English department students and offers practical recommendations for integrating these strategies into diverse academic disciplines.Keywords: Collaborative Learning, Reading Comprehension, EFL, Non-English Department Student